Hyperbilirubinemia following lenalidomide administration. Issue 5 (13th March 2018) - Azmy, Veronica; Neparidze, Natalia
Key Clinical Message: Asymptomatic hyperbilirubinemia in a patient with no underlying liver disease or renal impairment while on lenalidomide therapy may be attributable to the unmasking of previously undiagnosed Gilbert's syndrome, as previously shown in the literature. The hyperbilirubinemia should resolve after discontinuation of the drug. Abstract : Asymptomatic hyperbilirubinemia in a patient with no underlying liver disease or renal impairment while on lenalidomide therapy may be attributable to the unmasking of previously undiagnosed Gilbert's syndrome, as previously shown in the literature. The hyperbilirubinemia should resolve after discontinuation of the drug.